Tanreqing injection inhibits dengue virus encephalitis by suppressing the activation of NLRP3 inflammasome - Hefei Huang; Xuemei He; Lingzhu Shi; Jingtao Yu; Zibin Lu; Huihui Cao; Jinying Ou; Xi Chen; Lijun Yan; Jiabin Yang; Wei Zhao; Junshan Liu; et al. (BMC, 2024)
Abstract Background Encephalitis caused by dengue virus (DENV) is considered a manifestation of severe dengue. Tanreqing injection (TRQ) is a well-known Chinese patented medicine, which has been used to treat brain-related disorders by inhibiting inflammation. Nevertheless, the effects of TRQ on DENV encephalitis have not been studied. The aim of this study was to evaluate the effects of TRQ on DENV encephalitis and to explore its potential mechanisms. Methods The cytotoxicity of TRQ was examined by MTT assay, and the anti-DENV activities of TRQ in BHK-21 baby hamster kidney fibroblast were evaluated through CCK-8 and plaque assays. The expression levels of NO, IL1B/IL-1β, TNFα and IL6 were measured by qRT‒PCR and ELISA in the BV2 murine microglial cell line. The inhibitory effects of TRQ on NLRP3 inflammasome activation in BV2 cells were examined by Western blotting, qRT‒PCR and ELISA. The effects of TRQ on HT22 mouse hippocampal neuronal cells were examined by CCK-8 assay, morphology observation and flow cytometry. Moreover, a DENV-infected ICR suckling mouse model was developed to investigate the protective role of TRQ in vivo. Results TRQ decreased the release of NO, IL6, TNFα and IL1B from BV2 cells and inhibited the activation of NLRP3. The presence of the NLRP3 agonist nigericin reversed the anti-inflammatory activities of TRQ. Furthermore, TRQ inhibited the death of HT22 cells by decreasing IL1B in DENV-infected BV2 cells. In addition, TRQ significantly attenuated weight loss, reduced clinical scores and extended the survival in DENV-infected ICR suckling mice. Critically, TRQ ameliorated pathological changes in ICR suckling mice brain by inhibiting microglia and NLRP3 activation and decreasing the production of inflammatory factors and the number of dead neurons. Conclusion TRQ exerts potent inhibitory effects on dengue encephalitis in vitro and in vivo by reducing DENV-2-induced microglial activation and subsequently decreasing the inflammatory response, thereby protecting neurons. These findings demonstrate the potential of TRQ in the treatment of dengue encephalitis.